Analytical validation of a new point‐of‐care assay for serum amyloid A in horses. (19th February 2018) - Schwartz, D.; Pusterla, N.; Jacobsen, S.; Christopher, M. M.
Summary: Background: Serum amyloid A (SAA) is a major acute phase protein in horses. A new point‐of‐care (POC) test for SAA (Stablelab) is available, but studies evaluating its analytical accuracy are lacking. Objectives: To evaluate the analytical performance of the SAA POC test by 1) determining linearity and precision, 2) comparing results in whole blood with those in serum or plasma, and 3) comparing POC results with those obtained using a previously validated turbidimetric immunoassay (TIA). Study design: Assay validation. Methods: Analytical validation of the POC test was done in accordance with American Society of Veterinary Clinical Pathology guidelines using residual equine serum/plasma and whole blood samples from the Clinical Pathology Laboratory at the University of California‐Davis. A TIA was used as the reference method. We also evaluated the effect of haematocrit (HCT). Results: The POC test was linear for SAA concentrations of up to at least 1000 μg/mL (r = 0.991). Intra‐assay CVs were 13, 18 and 15% at high (782 μg/mL), intermediate (116 μg/mL) and low (64 μg/mL) concentrations. Inter‐assay (inter‐batch) CVs were 45, 14 and 15% at high (1372 μg/mL), intermediate (140 μg/mL) and low (56 μg/mL) concentrations. SAA results in whole blood were significantly lower than those in serum/plasma (P = 0.0002), but were positively correlated (r = 0.908) and not affected by HCT (P = 0.261); proportional negative bias was observed in samples with SAA>500 μg/mL. The difference between methods exceeded the 95% confidence interval of the combined imprecision of both methods (15%). Main limitations: Analytical validation could not be performed in whole blood, the sample most likely to be used stall side. Conclusion: The POC test has acceptable accuracy and precision in equine serum/plasma with SAA concentrations of up to at least 1000 μg/mL. Low inter‐batch precision at high concentrations may affect serial measurements, and the use of the same test batch and sample type (serum/plasma or whole blood) is recommended. Comparison of results between the POC test and the TIA is not recommended.